ANALISIS PENDAPATAN USAHATANI PADI SAWAH DENGAN POLA TANAM BENIH LANGSUNG DI DESA SIMAGAYA KECAMATAN BALAESANG KABUPATEN DONGGALA - Pratiwi, Maya; Damayanti, Lien; Howara, Dafina (AGROTEKBIS, 2018)
Simagaya village is one of rice production centers in Balaesang sub-district Donggala regency. Farmer in that village applied the system of direct seeds planting due to the high cost for labor. The determination of research location was purposive sampling because this village is one of rice production center. This research aims to identify the income of rice field farm by applying direct seeds plant method. This research was conducted on April to May 2017. The respondent determined by simple random sampling. The number of respondent was 32 out of 116 farmers. Analysis technique used is income analysis. The result of this research showed that the average production obtained on the land area of 0.72 Ha/PS is 1.235.93 Kg with selling price of Rp. 7000/Kg then the total income is Rp. 8.624.500 while the total cost is Rp. 4.319.037. It provides income of Rp. 4.308.463/0.72 Ha/PS in one planting season.Â Keywords : Income Analysis, Rice Paddy, Simagaya Village.